Reviews and Advances in Materials Processing - Gupta, Manoj (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Materials processing is the first, and a key, step in proper utilization of the composition of a given material and to realize the microstructural features that are intended to attain desired property levels for a given application. Both primary and secondary processing methods are equally important in tailoring the end properties of materials. In view of the crucial importance of the processing of materials, this Special Issue is intending to cover all innovative aspects of primary processing (solid phase, liquid phase, two phase, 3D printing, rapid solidification, etc.) and secondary processing (such as variations in extrusion, forging, rolling, equichannel angular extrusion, etc.) of materials (polymers/metal/ceramic-based, including their composites). Desirable attributes expected for submission will be processing-microstructure-property interrelations.